Investigation of Woven Orientation of Natural Fiber by Finite Element Method - Mohamad Azani, Muhammad Arfan; Mohamad, Zaleha (Journal of Advanced Mechanical Engineering Applications, 2022)
Natural fibre is recognized for having a lower density than synthetic fibre, as well as being cheaper, more plentiful, and most significantly, renewable. Aside from that, thanks to advancements in current technology, natural fibre processing is also more cost-effective and environmentally friendly than synthetic material. Due to the various applications of natural fibres especially bamboo and kenaf in several industries, they may be exposed to cyclic load which based on their preferred applications. In this study, a finite element analysis using numerical simulation had implemented to investigate the characteristics of notch at crack tip opening angle for bamboo and kenaf woven fibre as well as the deformation, strain, stress and mode I stress intensity factor (SIF) criteria. Consequently, strength criteria of the woven fibre also could be observed. So, the numerical modelling of bamboo and kenaf woven fibres was performed under quasi static loading method. This simulation focuses on the three types of woven orientations, which include 0°/90°, 30°/-60°, and 45°/-45°, with each specimen having two different materials and being tested using mode 1 compact tension tensile test according to ASTM D5045 standard. The result shows kenaf is stronger in term of strength as well as 0°/90° specimen with reasonable grounds for the statement.